(untitled) (Comparative & International Education Series, 2022)
With the increasing transnational student movement and changing nature of work, the need for universities to produce work-ready international student graduates as transnational human capital has become a major concern for all countries including Malaysia. This chapter aims, via content analysis and interviews, to (a) explore the Work-Based Learning initiatives (WBLi’s) integrated into the postgraduate programmes for international students in Malaysia and (b) appraise the capabilities of the country’s universities to facilitate WBLi’s. As the outcomes from eleven sample Malaysian universities (both public and private) have revealed, the WBL practices here are found to be still in a developing/emerging process. It can be accentuated by extending the scope of WBLi’s scope in the curricula, increasing industrial collaboration, and bringing necessary changes in relevant policies.